The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.jpcb.6b07248
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin Diphosphate Activation in 1-Deoxy-d-xylulose 5-Phosphate Synthase: Insights into the Mechanism and Underlying Intermolecular Interactions

Abstract: 1-Deoxy-D-xylulose 5-phosphate synthase (DXS) is a thiamin diphosphate (TDP) dependent enzyme that marks the beginning of the methylerythritol 4-phosphate isoprenoid biosynthesis pathway. The mechanism of action for DXS is still poorly understood and begins with the formation of a thiazolium ylide. This TDP activation step is thought to proceed through an intramolecular deprotonation by the 4′-amino-pyrimidine ring of TDP; however, this step would occur only after an initial deprotonation of its own 4′-amino g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 96 publications
0
47
0
Order By: Relevance
“…In physiological conditions, it was observed that hTK requires the presence of the thiamine diphosphate (ThDP) cofactor as co-catalytic agent. [1,2,[32][33][34] An example of a reaction catalyzed by hTK is reported in Scheme 1, which also represents the reaction studied in the present work. [1,13,[17][18][19][20] Since the product of this last process is a highly reactive species, ThDP-dependent enzymes are widely adopted in relevant processes for several chemoenzymatic synthesis involving the formation or the cleavage of CÀ S, CÀ N, CÀ C and CÀ O bonds, [21][22][23][24][25][26][27][28] as well as the sustainable and ecofriendly asymmetric carboligation of both aliphatic and aromatic compounds.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In physiological conditions, it was observed that hTK requires the presence of the thiamine diphosphate (ThDP) cofactor as co-catalytic agent. [1,2,[32][33][34] An example of a reaction catalyzed by hTK is reported in Scheme 1, which also represents the reaction studied in the present work. [1,13,[17][18][19][20] Since the product of this last process is a highly reactive species, ThDP-dependent enzymes are widely adopted in relevant processes for several chemoenzymatic synthesis involving the formation or the cleavage of CÀ S, CÀ N, CÀ C and CÀ O bonds, [21][22][23][24][25][26][27][28] as well as the sustainable and ecofriendly asymmetric carboligation of both aliphatic and aromatic compounds.…”
Section: Introductionmentioning
confidence: 89%
“…Upon binding, X5P engages in several hydrogen bonds with the active site sidechains, as evidenced in Figure 1. [1,18,33,39] In order to prevent large artificial movements of the amino acids in the quantum cluster model, the coordinate-locking scheme has been adopted in which amino acid residues are usually truncated at Cα atoms and these are fixed during geometry optimizations, being the overall structure close to the experimental one. Atom O4 is involved in hydrogen bonds with residues Asp424B, His37A and His109 A, while atom O3 is involved in a hydrogen bond with His258A.…”
Section: The Qm Cluster Modelmentioning
confidence: 99%
See 3 more Smart Citations